Blue ribbon science fair projects - Iritz, Maxine Haren. 4 0 16; 5 (New York : Tab Books, 1991)
Readers learn about the organization and development of school science projects from their beginnings as vague concepts, to the experiment and testing stages, and finally to completion and display.
Includes bibliographical references (p. 115-117) and index.
Horn Book;Book Report
Young Adult;Young Adult
Keywords: 2 -- 0; 6; Experiments.;Experiments. -- Science projects;Science projects.;Science;Science projects.;Science -- Juvenile literature; 20; 2